New Directions in Industrial Relations Research? - Sappey, J.; Sappey, R.; Burgess, John (Pacific Employment Relations Association, 2014)
Traditionally employment (or industrial) relations, has been associated with the management of either collective or individual conflict in the workplace. In recent years, the focus has opened out to consider the benefits of high performance working on productivity, but also the wider social implications for individuals and their dependents. The workplace provides not only the money that we need to support ourselves and our families but it can also provide purpose, status, and friendship, allowing people to develop new skills, both technical and social. The ability of line managers to manage employment relations on a day-to-day basis and to get the best from their staff has implications for innovation, productivity, quality and reliability, and ultimately levels of growth at a national level and our ability to compete on the global stage. With so much invested in work by managers and employees individually, employment relations has never been so important.